TANGGAPAN WISATAWAN PADA ATRAKSI TARI ZAPIN DI KAWASAN WISATA ISTANA ISTANA ASSERAYAH ALHASYIMIAH - Asmalia Okta Sari; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Respon in the world of tourism is the opinion of way of view of visitors and tourists in understanding a tourist destination. This research was conducted in attraction zapin dance, Rempak Village, Siak District. This study aims to determine the respons of tourist to the attraction zapin dance in the palace touristarea asserayah alhasyimiah in siak district. This research uses quantitative descriptive method to process the data obtained in the field through interviews, observations and questionnaires. All the information collected and studied to become a unifed whole. As for the sample in research 100 respondent. The determinsntion of respondents with accidental sampling. Data collection techniques used are observations, interview, questionnaires, using likert scale as ameasuring tool. Based on the result of research that has been done the attraction of zapin dance with sub variable uniqueness, authenticity and value interesting research conclusions.Keywords: Respon of tourists, Attraction, Zapin dance